Zetaproteobacteria Pan-Genome Reveals Candidate Gene Cluster for Twisted Stalk Biosynthesis and Export - Koeksoy, Elif; Bezuidt, Oliver M.; Bayer, Timm; Chan, Clara S.; Emerson, David (Frontiers in Microbiology, 2021)
Twisted stalks are morphologically unique bacterial extracellular organo-metallic structures containing Fe(III) oxyhydroxides that are produced by microaerophilic Fe(II)-oxidizers belonging to the Betaproteobacteria and Zetaproteobacteria. Understanding the underlying genetic and physiological mechanisms of stalk formation is of great interest based on their potential as novel biogenic nanomaterials and their relevance as putative biomarkers for microbial Fe(II) oxidation on ancient Earth. Despite the recognition of these special biominerals for over 150 years, the genetic foundation for the stalk phenotype has remained unresolved. Here we present a candidate gene cluster for the biosynthesis and secretion of the stalk organic matrix that we identified with a trait-based analyses of a pan-genome comprising 16 Zetaproteobacteria isolate genomes. The “stalk formation in Zetaproteobacteria” (sfz) cluster comprises six genes (sfz1-sfz6), of which sfz1 and sfz2 were predicted with functions in exopolysaccharide synthesis, regulation, and export, sfz4 and sfz6 with functions in cell wall synthesis manipulation and carbohydrate hydrolysis, and sfz3 and sfz5 with unknown functions. The stalk-forming Betaproteobacteria Ferriphaselus R-1 and OYT-1, as well as dread-forming Zetaproteobacteria Mariprofundus aestuarium CP-5 and Mariprofundus ferrinatatus CP-8 contain distant sfz gene homologues, whereas stalk-less Zetaproteobacteria and Betaproteobacteria lack the entire gene cluster. Our pan-genome analysis further revealed a significant enrichment of clusters of orthologous groups (COGs) across all Zetaproteobacteria isolate genomes that are associated with the regulation of a switch between sessile and motile growth controlled by the intracellular signaling molecule c-di-GMP. Potential interactions between stalk-former unique transcription factor genes, sfz genes, and c-di-GMP point towards a c-di-GMP regulated surface attachment function of stalks during sessile growth.